Considering Participant Motivation In Knowledge Management Projects - Whittom, Allen; Roy, Marie-Christine (Journal of Knowledge Management Practice, 2009)
Even though the majority of organizations have initiated Knowledge Management projects, turning them into successes still remains a great challenge. There is probably a variety of reasons why these projects fail, many being related to improper technology implementation. However, a major cause of failure has often been attributed to the lack of motivation of participants. In this paper, we lay out the principles underlying motivation theories and link them to more effective KM project management practices. Specifically, we explain how intrinsic and extrinsic rewards must be carefully planned and dosed depending on the type of project and the environment in which it is implemented. We also conclude that all KM projects can benefit from greater participant internal motivation, and therefore encourage the use of intrinsic rewards and a closer analysis of psychological work related factors.